Traveling waves solutions to general isothermal diffusion systems. (December 2015) - Qi, Yuanwei
Abstract: This article studies propagating traveling waves in a class of reaction–diffusion systems in one dimensional space which model isothermal diffusion, bio-reactor and auto-catalytic chemical reactions. In addition, the reaction terms are non-KPP, which denies a linear theory for determining minimum speed. By using novel techniques, it is shown that the minimum speed depends, for a given reaction term, on the size of ratio of diffusion coefficients D in a subtle way; with the case D > 1 demonstrating very different properties from that of D < 1 .